First Detection of Radio Emission from the Intermediate-mass Black Hole in POX 52: Deep Multiband Observations with ATCA and VLA - Qi Yuan; Hengxiao Guo; Minfeng Gu; Jamie Stevens; Philip G. Edwards; Yongjun Chen; Wenwen Zuo; Jingbo Sun; Jun Yang; Paulina Lira; Tao An; Renzhi Su; et al. (The Astrophysical Journal)
We present the first multiband centimeter detection of POX 52, a nearby dwarf galaxy believed to harbor a robust intermediate-mass black hole. We conducted the deep observations using the Australia Telescope Compact Array (ATCA), spanning frequencies from 4.5 to 10 GHz, as well as the sensitive observations from the Karl G. Jansky Very Large Array (VLA) operating in its most extended A configuration at S band (2–4 GHz) and C band (4–8 GHz). In the ATCA observations, the source shows a compact morphology, with only one direction marginally resolved. The higher resolution of the VLA allowed us to slightly resolve the source, fitting it well with a two-dimensional Gaussian model. The detected radio emission confirms the presence of active galactic nucleus (AGN) activity, indicating either a low-power jet or AGN-driven winds/outflows. Our dual-epoch observations with ATCA and VLA, together with previous nondetection flux density upper limits, reveal radio emission variability spanning two decades. In addition, we find that POX 52 aligns well with the low-mass extension of the fundamental plane for high-accretion, radio-quiet massive AGNs.